World Health Organization Member States and Open Health Data: An Observational Study (Epidemiology, Biostatistics, and Public Health, 2022)
BackgroundOpen health data has implications for clinical care, research, public health, and health policy at regional, national, and global levels. No published attempts have been made to determine, collectively, whether WHO member states and governments have embraced the promise and effort required to officially share open health data. The observational study will provide evidence that World Health Organization (WHO) member states individually and collectively have adopted open data recommended principles, providing access to open health data.MethodsUsing the WHO list of member states (n=194), the researchers identified the presence of open health data or initiatives. With each country, the following types of official government web pages were recorded: a Ministry of Health web page; a conspicuous link on a government web page to open health data; additional government health web sites; national government-sponsored open data repositories; unique attributes of national health data web sites; and adherence to the principles of open government data for health. A supplemental PDF file provides a representation of data used for analysis and observations. Our complete data is available at: https://goo.gl/Kwj7mbObservations and DiscussionOpen health data is easily discoverable in less than one-third of the WHO member states. 13 nations demonstrate the principle to provide comprehensive open data. Only 16 nations distribute primary, non-aggregated health data. 24 % of the WHO observed member states are providing some health data in a non-proprietary formats such as comma-separated values. The sixth, seventh, and eighth open government data principles for health, representing universal access, non-proprietary formats, and non-patent protection, are observed in about one-third of the WHO member states. While there are examples of organized national open health data, no more than a one-third minority of the world’s nations have portals set up to systematically share open health data. At least 15 WHO member states are observed to not even have a government health ministry representation online.ConclusionWe hope the data collected in our Google Sheet and the discussion provided in this paper will generate international interest and advocacy for open health data.